Pengaruh Partisipasi Anggaran, Asimetri Informasi dan Preferensi Risiko Pada Senjangan Anggaran - Putri, Ida Ayu Dwiastami; Mimba, Ni Putu Sri Harta (E-Jurnal Akuntansi, 2018)
Budgeting is an important aspect not only for private sector, but also for public sector. In governmental organizations the budget is a guideline for financial management. This study aims to determine the effect of budgetary participation, information asymmetry and risk preference on budgetary slack in SKPD in Badung Regency. This research was conducted on 35 SKPD in Badung Regency. Sampling using purposive sampling method. The number of samples taken as many as 70 employees, consisting of Head of SKPD and Head of Sub Division of Finance of each SKPD . Data collection was done through questionnaires and interviews. The analysis technique used in this research is multiple linear regression analysis. Based on the results of the analysis found that the participation of budgeting and information asymmetry have a positive effect on budgetary slack, it shows that the higher level of participation and information asymmetry incrase the budgetary slack. Risk preference has a negative effect on budgetary slack in Badung Regency SKPD . This suggests that budget compilers choose smaller risks and they make budgets are with their true potential and can causethe budgetary slack.